Effect of Customer Bonding and Social Media Marketing on Purchase Intention of SMEs Product - Jasin, Mochammad (IJOSMAS, 2022)
This study aims to determine the effect of customer bonding and social media marketing on the purchase intention of SMEs products. The sample of respondents in this study were all consumers of SMEs products, totaling 350 people. Determination of the sample using simple random sampling method. Data analysis using path analysis or (path analysis). Analysis of research data using Structural Equation Modeling (SEM) with software tools SmartPLS 3.0. Data was obtained by distributing online questionnaires distributed through social media. The results of the analysis show that the social media marketing variable has a positive and significant effect on purchase intention. Social media marketing has a positive and significant effect on customer bonding. Customer bonding has a positive effect and significant to purchase intention.